Human Interface and the Management of Information. Information and Knowledge in Applications and Services 16th International Conference, HCI International 2014, Heraklion, Crete, Greece, June 22-27, 2014. Proceedings, Part II - Yamamoto, Sakae; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The two-volume set LNCS 8521 and 8522 constitutes the refereed proceedings of the Human Interface and the Management of Information thematic track, held as part of the 16th International Conference on Human-Computer Interaction, HCII 2014, held in Heraklion, Greece, in June 2014, jointly with 13 other thematically similar conferences. The total of 1476 papers and 220 posters presented at the HCII 2014 conferences were carefully reviewed and selected from 4766 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems.The papers accepted for presentation thoroughly cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. This volume contains papers addressing the following major topics: e-learning and e-education; decision support; information and interaction in aviation and transport; safety, security and reliability; communication, expression and emotions; art, culture and creativity; information and knowledge in business and society.
Decision support -- E-learning and e-education -- Information and interaction in aviation and transport -- Safety, security and reliability -- Communication, expression and emotions -- Art, culture and creativity -- Information and knowledge in business and society.
Keywords: User interfaces (Computer systems).; Application software; Information storage and retrieval; Education—Data processing; User Interfaces and Human Computer Interaction; Computer Applications; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Computers and Education